The effect of spray-drying temperature on Centella asiatica extract-β cyclodextrin-maltodextrin nanoparticle characteristics and stability - Aditya Trias Pradana; Roisah Nawatila; Fawandi Fuad Alkindi; Ni Putu Resa Darmayani; Eka Desi Susanti (Pharmaciana, 2021)
Centella asiatica extract has low solubility in water. Material modification needs to be conducted to increase the dissolution rate of Centella asiatica extract. The particle size reduction to nano-size was carried out to increase surface contact with aqueous media. High surface contact was expected to increase the solubility and absorption rate. Nanoparticles were prepared with 34% maltodextrin and 6% β-cyclodextrin as a stabilizer and dried by a spray-drying method. High temperature in the spray drying process can affect the physical and chemical characteristics of the nanoparticles, so the inlet temperature in this study was observed as parameter variations, on 140oC, 150oC, and 160oC. The formed nanoparticles then being tested on several parameters, including physical appearance, moisture content, particle size, shape, and morphology. The chemical stability of the active ingredients during the drying process was assessed from the pH value changes and the content of quercetin as an antioxidant post drying process, compared to the initial content. The test results show that the nanoparticles have been formed. The inlet temperature of 160oC produced the most physically optimum spherical nanoparticles, with a particle size of 191.533 ± 18.791 nm and relatively homogeneous with a polydispersity index (PDI) value of 0.113 ± 0.057. However, temperatures that are too high indicate poor chemical stability. The poor chemical stability can be seen from the quercetin content that decreased significantly after the drying process, until the remaining 53.87 ± 0.55% and 49.52 ± 0.97% for temperatures of 140oC and 160oC, respectively. These results indicate that the combination of β-cyclodextrin and maltodextrin can not encapsulate and maintain the stability of the active ingredients during the spray drying process. A significant reduction of inlet temperature is needed to get dry nanoparticles with the most optimum physical mixture and chemical stability.